ANALISIS HASIL KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA PADA PEMBELAJARAN DI ERA COVID-19 - Imas Nadiah; Pujia Siti Balkist; Yanti Mulyanti (UJMES (Uninus Journal of Mathematics Education and Science), 2022)
This study aims to describe the students’ mathematical critical thinking skills in online learning. This type of research is a case study with a qualitative approach and descriptive qualitative research design and data collection techniques in the form of testing and interviews. The subjects in this study were three students 7 grade students of Junior High School 1 Sukaraja, taking the subject in this study using purposive sampling. Based on the results of the study, that students who have the ability to think critically mathematically high category that is collecting and compiling information needed, find ways that can be used to solve problems, analyze data and draw conclusions and similarities needed. Students who have the ability to think critically mathematically categories are fulfilling one to two components of mathematical critical thinking that is finding ways that can be used to solve problems analyze data. Students who have low category mathematical critical thinking skills do not meet the four components of mathematical critical thinking ability.